Gender Diversity Policies for Enhanced Service Delivery among Chartered Universities in Kenya - Maina, Charity Nyambura; Nzioki, Susan; Mugambi, Kenneth (International Journal of Professional Practice, 2024)
Integrating gender diversity policies into organizational structures is vital for sustainable development and climate action. However, there is a notable gap in the implementation of these policies, especially in Kenyan chartered universities. This study evaluated the influence of gender diversity policy implementation on service delivery in Kenyan chartered universities. The hypothesis: there is no statistically significant relationship between gender diversity policy implementation and service delivery among chartered universities in Kenya, was tested. The researcher employed a descriptive survey design, and the target population was 15,545 administrative staff and full-time lecturers. Using stratified and purposive sampling techniques, the population was divided into teaching and non-teaching staff. Random sampling technique was used to select a sample size of 390 respondents, comprising of 120 teaching staff and 269 administrative staff was calculated using Yamane (1967) formula. A pilot study was conducted to test the validity and reliability of the research instruments. The study employed Findings revealed that universities with effective gender diversity policies demonstrated enhanced service delivery, efficiency and effectiveness. Descriptive analysis showed moderate correlation among variables, particularly supporting flexible working hours for nursing mothers, gender-mainstreaming awareness, and prohibition of sanctions related to pregnancy or marital status. Statistical analysis indicated a significant positive correlation (R = 0.514) between gender diversity policy implementation and service delivery. The study concluded that gender diversity policy implementation significantly enhances service delivery in Kenyan chartered universities. The study recommends that universities develop practical and comprehensive gender diversity framework, with continuous monitoring and evaluation, implementation, training, and sensitization programs that guarantee commitment to gender diversity initiatives.